The Influence of Budgeting Objectives Characteristics on The Performance of Local Government Officers - Istiyani Istiyani (Jurnal Akuntansi dan Bisnis, 2011)
The aims of this research are to examine the influence of budgeting objectives characteristics on the performance of Local Government of Temanggung Regency. Sampling technique used in this research was purposive sampling. This method was applied since sample was selected purposively based on a certain criteria as Local Government Officers in the middle up to lower level who were also commitment maker in the sense that they participate in budgeting and its implementation and also as staff in charge of budget arrangement. Number of sample processed in the research is 146 samples and processed using SPSS program to examine hypothesis. The Research found out that from five variables of budgeting objectives characteristics, four variables (the clarity of objectives, participation, feedback and objective achievement difficulties) significantly influence the performance of Local Government Officers of Temanggung Regency.